A study of awareness of ocular complications of diabetes among students - Puri, Sanjeev Kumar; Elangovan, Suma (International Journal of Research in Medical Sciences, 2016)
Background: Diabetes mellitus has become a major public health problem throughout the world. The aim was to study the awareness of ocular complications due to diabetes mellitus among students. Methods: A questionnaire based study was conducted among 430 students (non-medical). The questions tested their awareness about diabetes mellitus and also about the potential ocular complications of the disease. Results: Out of 430 students 73.02% (314/430) have heard about diabetes mellitus but they did not know that it can affect the eye and can lead to blindness. They were unaware that regular eye check-up is important in diabetes mellitus. 18.83% (81/430) were aware about the disease and its potential to cause vision threatening complications. 8.13% (35/430) were not aware about diabetes mellitus. Overall only 18.83% had some basic knowledge about diabetes and its complications. Conclusions: The level of awareness about ocular complications due to diabetes mellitus is low among students. Therefore steps should be taken to increase the awareness about diabetes and inculcate some basic knowledge about its potential complications especially vision threatening diabetic retinopathy. It should be strongly emphasized that periodic eye check-up is important to prevent needless blindness and visual dysfunction. Keywords: Glaucoma, Non-medical students, Awareness